(untitled) (Prostor, 2024)
The dissertation investigates the relation between the architectural form of the museum and place with a specific analytical approach based on key parameters that define the museum’s relation to place. To examine this relation, the research encompasses the processes that relate the museum to place based on in-situ museum interpretation, and the approaches for in-situ protection, interpretation and presentation of place.